Project management for the development of Internet banking in second-tier banks of the Republic of Kazakhstan, as one of the ways of improving the relationship with customers (Journal of Economic Research & Business Administration, 2016)
Currently the development of the market and increased competition in the Kazakh economy is forcing banks to look for competitive advantages. Such advantages can provide either internal production efficiency, or bet-ter compared with competitors market orientation. The introduction of advanced technologies is a key issue in the development of the Bank, in this case, the most important in the process of IT implementation is to tie them to the goals and strategies of the Bank. One of the developing areas of new technology is the development of Internet banking and mobile banking. One of the reasons for the development of projects in this direction is the uneven distribution of the population and service points, moreover, most banks are not willing to open branches in rural areas. The development of online channels and remote banking service in the future will contribute to a broad base of new customers.
Keywords: Project management; internet banking; mobile banking; IT technology; projects; bank